The Catechetical School in Alexandria - Oliver, Willem H. (2015)
During her Golden Era, Alexandria, the Delta City of Egypt, was the pride of Africa in that she was larger than the two other world cities of the Roman Empire - Rome and Antioch - and also the unrivalled intellectual centre of the (Greco-)Roman world. Her schools, including the Didaskaleion - the Catechetical School - outshone the schools of her rivals by far. During the first half of the 1st century CE and specifically after the destruction of the temple and the fall of Jerusalem in 70 CE, many Jews fled their home country for different parts of the Roman Empire, like Transjordan, Syria and Africa. A number of these Jews - later called Christians - believed in Jesus of Nazareth. In Alexandria, these believers were confronted with different religions, cults and philosophies. The Didaskaleion was founded to rival these religions and cults and to provide the students with the necessary basis for their newly found religion. The lack of literature, on the one hand, and the credibility of the extant literature, on the other, caused great difficulty in reasoning with authority on the Didaskaleion. This is part one of two articles, the second one being constructed around the heads of the School.Intradisciplinary and/or interdisciplinary implications: Research about Africa done by Africans (inhabitants of Africa) need to increase because, in many ways Africa, is silent or silenced about her past. The fundamental question is: Can anything good come out of Africa?' My answer is, Yes! Come and see.' Therefore these two articles attempt to indicate the significance of Africa, which was actually the place where Christian Theology was founded. This has intra- as well as interdisciplinary implications. In this case the investigation is done from a theological perspective.
Keywords: Africa; Alexandria; Catechetical School; Early Church